2016
DOI: 10.1097/ijg.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Excision of Tenon Capsule in Pediatric Trabeculectomy

Abstract: Excision of the Tenon capsule could help achieve better IOP control in pediatric glaucoma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“… 31 Since a small portion of Tenon's was removed at the location of the stent, with blunt posterior dissection of both the subconjunctival and sub-Tenon's spaces, MMC injection can reach the inner conjunctival surface, both sides of the remaining Tenon's and the outer scleral surface, inhibiting fibroblast proliferation and scarring from all of these potential sources. Finally, a partial tenectomy was performed, which has been shown to reduce the frequency of encapsulated blebs following trabeculectomy in pediatric patients 33 and may reduce the risk of early stent obstruction. 27 These modifications likely promoted the formation of excellent diffuse, posterior, and avascular bleb morphologies.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Since a small portion of Tenon's was removed at the location of the stent, with blunt posterior dissection of both the subconjunctival and sub-Tenon's spaces, MMC injection can reach the inner conjunctival surface, both sides of the remaining Tenon's and the outer scleral surface, inhibiting fibroblast proliferation and scarring from all of these potential sources. Finally, a partial tenectomy was performed, which has been shown to reduce the frequency of encapsulated blebs following trabeculectomy in pediatric patients 33 and may reduce the risk of early stent obstruction. 27 These modifications likely promoted the formation of excellent diffuse, posterior, and avascular bleb morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of failure following glaucoma filtering surgeries are related to the proliferation of fibroblasts, synthesis of extracellular matrix, and subsequent development of subconjunctival fibrosis [ 6 ]. Research has been carried out to investigate the potential for excising Tenon’s capsule [ 7 , 8 ], placing valve implants above Tenon’s [ 9 ], and locating filtering blebs under Tenon’s [ 10 ]. However, it seems that the most important element to a successful glaucoma filtering surgery is the use of antimetabolites [ 1 , 11 , 12 ].…”
Section: Peri-operative/adjunctive Use Of Antifibrotic Agentsmentioning
confidence: 99%
“…Therefore, these studies showed the potential influence on scar formation by interfering with conjunctiva and Tenon’s capsule and inspired us to study whether dissecting subconjunctival tissues at different depths influences subconjunctival fibrosis. Furthermore, excision of Tenon’s capsule during trabeculectomy helps in preventing fibrosis and enhances the chances of success [4]. Tenon’s capsule needs to be excised during filtration surgery to alleviate fibroblastic response, especially for the thick and active Tenon’s capsule [23].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive external mini-glaucoma shunt implantation with less conjunctival dissection potentially causes less conjunctival scarring [3]. Moreover, tenonectomy in trabeculectomy may help reduce fibrosis and therefore improves the success rate [4]. These results inspired us to explore whether dissecting subconjunctival tissues at different depths influences scar formation.…”
Section: Introductionmentioning
confidence: 99%